2017
DOI: 10.3389/fmicb.2017.00474
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in Host–Pathogen Interactions: Subversion of Mammalian Cell Functions by Protozoan Parasites

Abstract: Pathogens have evolved mechanisms to modulate host cell functions and avoid recognition and destruction by the host damage response. For many years, researchers have focused on proteins as the main effectors used by pathogens to hijack host cell pathways, but only recently with the development of deep RNA sequencing these molecules were brought to light as key players in infectious diseases. Protozoan parasites such as those from the genera Plasmodium, Toxoplasma, Leishmania, and Trypanosoma cause life-threate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 71 publications
(87 reference statements)
0
29
0
Order By: Relevance
“…Very recently, Dandewad and coworkers described the retrograde mechanism that involves a transport of human miRNA-RISC complexes into Plasmodium falciparum cells and a further regulatory mechanism of the parasite mRNA targets [139]. These combined mechanisms demonstrate an intimate molecular cross-communication between the malaria parasite and its host where ncRNAs are important players and could be extensive to other protozoa [140,141] and helmintic parasites [142].…”
Section: Mammalsmentioning
confidence: 99%
“…Very recently, Dandewad and coworkers described the retrograde mechanism that involves a transport of human miRNA-RISC complexes into Plasmodium falciparum cells and a further regulatory mechanism of the parasite mRNA targets [139]. These combined mechanisms demonstrate an intimate molecular cross-communication between the malaria parasite and its host where ncRNAs are important players and could be extensive to other protozoa [140,141] and helmintic parasites [142].…”
Section: Mammalsmentioning
confidence: 99%
“…Recently, two novel "star non-coding RNAs (ncR-NAs)", namely long non-coding RNA (lncRNA) and circular RNA (circRNA), have been reported to play pivotal role in the interaction between hosts and bacteria [25,26], viruses [27][28][29][30] and parasites [31][32][33]. For example, using the RNA-seq technique, the expression profiles of mRNAs, lncRNAs and circRNAs of tracheal tissues during Cryptosporidium baileyi infection were studied, and functional analysis of these differentially expressed RNAs were related to the immune system process, immune response and leukocyte activation, tight junction and glycerolipid metabolism, suggesting the important role of these RNAs in interaction between chickens and C. baileyi [33].…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulation of several ncRNAs upon infection with MVs also raise interesting questions on the role of this class of RNAs in L. monocytogenes infection. Several reports on ncRNAs suggested that the regulatory RNAs used by intracellular pathogens may aid to survive and evade immune responses (56,57).…”
Section: Discussionmentioning
confidence: 99%